Lattice-induced transparency in planar metamaterials - Manjappa, Manukumara (2017)
Lattice modes are intrinsic to periodic structures and they can be easily tuned and controlled by changing the lattice constant of the structural array. Previous studies have revealed the excitation of sharp absorption resonances due to lattice mode coupling with the plasmonic resonances. Here, we report an experimental observation of a lattice-induced transparency (LIT) by coupling the first-order lattice mode (FOLM) to the structural resonance of a terahertz asymmetric split ring resonator. The observed sharp transparency is a result of the destructive interference between the bright mode and the FOLM assisted dark mode. As the FOLM is swept across the metamaterial resonance, the transparency band undergoes a large change in its bandwidth and resonance position. We propose a three-oscillator model to explain the underlying coupling mechanism in LIT system that shows good agreement with the observed results. Besides controlling the transparency behavior, LIT also shows a huge enhancement in its Q factor and exhibits a high group delay of 28 ps with an enhanced group index of 4.5 x 104, which could be pivotal in ultrasensitive sensing and slow-light device applications.